Efeitos de um derivado semissintético do [6]-gingerol na autofagia e apoptose em células de câncer de mama - Dulcey, Liany Johanna Luna (2017)
In this work, we describe a semisynthetic derivative of [6]-gingerol called SSi6, which induces cytotoxic effects on the MDA-MB-231 breast tumor, showing a greater selectivity for these cells when compared to the non-tumor MCF-10A , In addition, the substance was determined to induce autophagy and apoptosis in tumor cells, with less pronounced effects on non-tumor cells. The coexistence of both events (autophagy and apoptosis) was demonstrated by flow cytometry, which evidenced an increase in the percentage of apoptotic cells after 24 hours of treatment, these results were also confirmed by the analysis of the gene and protein expression of caspase-3 using Real-time PCR and western blotting respectively. Induction of autophagy in SSi6-treated cells has been demonstrated through acid vesicle organelle (AVOs) detection assays and the expression of genes encoding the LC3-I and II microtubule-associated proteins to quantify the abundance of autophagosomes in MDA-MB-231 cells. Thus, these results indicate that SSi6 has the potential to induce autophagy and apoptosis, as well as antitumor and antimetastatic properties in MDA-MB-231 breast tumor cells.